Improvement to the scanning electron microscope image adaptive Canny optimization colorization by pseudo‐mapping. Issue 5 (19th August 2014) - Lo, T. Y.; Sim, K. S.; Tso, C. P.; Nia, M. E.
Abstract An improvement to the previously proposed adaptive Canny optimization technique for scanning electron microscope image colorization is reported. The additional feature, called pseudo‐mapping technique, is that the grayscale markings are temporarily mapped to a set of pre‐defined pseudo‐color map as a mean to instill color information for grayscale colors in chrominance channels. This allows the presence of grayscale markings to be identified; hence optimization colorization of grayscale colors is made possible. This additional feature enhances the flexibility of scanning electron microscope image colorization by providing wider range of possible color enhancement. Furthermore, the nature of this technique also allows users to adjust the luminance intensities of selected region from the original image within certain extent. SCANNING 36:530–539, 2014. © 2014 Wiley Periodicals, Inc.